Perception of father absence in family assessment and intervention: are they not involved because they don't want to be? - Castellano-Díaz, Regina; Martín Quintana, Juan Carlos; Alemán Ramos, Pedro Francisco (Journal of Social Work Practice, 2025)
Child protection services intervene with mothers, leaving fathers on the sidelines. However, fathers' involvement is beneficial. The aim is to explore fathers' and professionals' perceptions of the factors influencing fathers' involvement in family assessments and interventions. A qualitative design was used and 5 focus groups with 9 professionals, 10 mothers and 8 fathers, and 6 in-depth interviews with 6 fathers were carried out in Gran Canaria (Spain). A thematic content analysis was carried out using QSR NVivo 12. The category Determinants of paternal involvement in family assessment and intervention was obtained, made up of 3 subcategories: Personal characteristics of the father, Social characteristics and Influence of the mother on the father's decision. Fathers claim that fathers' personal characteristics condition their involvement, while professionals argue that it is due to mothers' influence. Implications for professional practice and work with men are discussed. This study is part of a funded research project.